Media and Vaccination Intentions During the COVID-19 Pandemic - Padilla-Bautista, Joaquín Alberto; Villanueva-Bustamante, Marcoantonio; Montañez Castillo, Flor Belén; Cardenaz-Rodríguez, Zenaida Graciela (Informes Psicológicos, 2023)
An effective means to counteract the effects caused by the SARS-CoV-2 pandemic are vaccination campaigns, which may face factors that reduce their effectiveness. Objective: To examine the influence of media on the intention to vaccinate against COVID-19. Method: To identify the media used and their influence on vaccination decisions, the Vaccination Intention instrument was employed, which exhibits reliability indices exceeding .8. A total of 563 Mexicans participated in a cross-sectional online study. Results: The Jonckheere-Terpstra test and the subset homogeneity test showed significant differences in vaccination intention based on the consulted media. Conclusions: Individuals who contrast information that enables them to have a critical stance have a higher intention to vaccinate, while those who consult only one media source have the lowest intention to vaccinate.
Keywords: COVID-19; Vaccination Intentions; Media; Vaccination; Pandemic; Coronavirus